In-house validation of a lamp kit for diagnosis of Plasmodium, Plasmodium falciparum and Plasmodium vivax in Vietnam - Nguyen Thi Hong Ngoc; Nguyen Thi Huong Binh; Nguyen Van Hong; Ngo Duc Thang; Nguyen Thu Huong; Tran Thanh Duong (Global Journal of Infectious Diseases and Clinical Research - Peertechz Publications, 2020)
Vietnam announced the elimination of malaria in 25 provinces in 2019 and and advance to eliminate malaria nationwide by 2030. Quick, accurate diagnosis and prompt treatment play a very important role in malaria eradication strategies. In this study, we developed the LAMP technique to detect Plasmodium spp., P. falciparum, P. vivax from different kinds of sample such as whole blood, dried blood spot, etc. The advantages of this method included high specificity, fast detection time, and simple equipment use. Primer set was designed for founding on 18S rRNA gene. A positive reaction was visualised with the naked eye, using the color indicator, Malachite Green.